DINAMIKA EJAAN AKSARA BALI DAN PENGGUNAAN BENTUK-BENTUK BERSAING - Eka Guna Yasa, Putu (Humanis; Volume 1. No. 1. November 2012, 2016)
The study "Dynamics Spelling Balinese and Use Forms Compete" aimed to determine the existence of the reality of the issues and challenges in today's Balinese script, and describes the factors underlying the occurrence of competing forms in several domains using Balinese script. The theory used in this study are phonological theory and the theory of sosiolingistik. The method used in this study through three stages, namely the stage of the supply of data, data analysis, and presentation of analysis results. Spelling Balinese script is now inherited by the people of Bali have undergone several dynamics. Spelling is used to first prototype dresta spelling or pairs, then in 1931 set spelling Schwartz, and the results of the Great Mother Bali The Assembly decided in 1957 to continue using prototype pairs dresta with some changes. Despite efforts to improve spelling Balinese script is done on a continuous basis but is still found in competing forms domains using Balinese script. The factors that cause these competing forms can be classified into two: internal and external factors. Internal factors caused by the level of knowledge of the science of linguistics, especially phonology and etymology of the word is not optimal. While external factors due to the onslaught of the Latin alphabet, Balinese script regeneration stagnation in the realm of the family, and a portrait of the Balinese language learning in there almof education is not optimal.
Keywords: Balinese, Phonology, and Dynamics Spelling